University extension in rural towns: enhancing community heritage in General Paz y Pila (Buenos Aires, Argentina) (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
This article provides an initial systematization of the experiences of dialogue of knowledge promoted by the Entramados rurales bonaerenses: patrimonio, territorios y comunidades Project of the National University of Quilmes and the Museums of Pila and General Paz (Buenos Aires). The text focuses on the description and analysis of the workshops held during 2023 with the aim of activating heritage processes and thus promoting socio-territorial transformations in these rural areas. We understand cultural heritage as an (inter)subjective and dynamic concept, which does not depend so much on the assets themselves as on the values attributed to them in each context and on the ability of different agents to determine what is and what is not part of the heritage collection. Thus, based on the premises of critical extension and participatory action research, stages, themes, and activities were defined with a focus on promoting well-being in the territories and reflections on their past, present, and future. Preliminary results show the uniqueness of the experiences located in rural Buenos Aires, the relevance of university outreach in these spaces, the adaptability of the dynamics, and the commitment of each community to the co-creation of its own heritage.
Keywords: university extension; cultural heritage; dialogue of knowledge; community; rural towns